The Internality of the Hadith on Patience towards the Psychological Resilience of Generation Z Muslims - Zahira Khairunnisa; Nasrulloh, Nasrulloh (Penerbit Hellow Pustaka, 2025)
Generation Z Muslims are growing up in a fast-paced digital era marked by complex psychosocial challenges, requiring strong mental resilience (psychological resilience). This study examines how the internalization of the value of ṣabr (patience) derived from the hadiths of the Prophet Muhammad (peace be upon him) contributes to the development of psychological resilience among this group. Employing a library research method with qualitative content analysis, the study analyzes authentic hadith texts alongside literature in psychology and Islamic psychology. The findings reveal that ṣabr in the hadith perspective is not a passive attitude but an active form of steadfastness involving self-control, perseverance, and sincere effort in facing trials, performing acts of obedience, and avoiding sinful behavior. The internalization of this value shapes cognitive schemas that transform perceptions of hardship by viewing difficulties as meaningful tests, means of expiation of sins, and pathways to closeness to Allah (SWT). This process functions as an effective form of religious coping, enabling Muslim Generation Z to engage in cognitive reframing, regulate negative emotions, and mitigate digital stressors such as social comparison and FOMO (Fear of Missing Out). Consequently, the internalization of ṣabr not only enhances resilience in real-life challenges but also fosters “digital resilience,” and the study concludes that integrating the value of ṣabr from hadith with contemporary psychological principles provides a robust spiritual framework for Muslim Generation Z to develop mental toughness, maintain psychological well-being, and adapt healthily to the complexities of the modern era.